2006
DOI: 10.1080/10473289.2006.10464431
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Assessment Modeling of Atmospheric Pollutants in the Southern Appalachian Mountains: Part II. Fine Particulate Matter and Visibility

Abstract: As part of the Southern Appalachian Mountains Initiative, a comprehensive air quality modeling system was developed to evaluate potential emission control strategies to reduce atmospheric pollutant levels at the Class I areas located in the Southern Appalachian Mountains. Six multiday episodes between 1991 and 1995 were simulated, and the skill of the modeling system was evaluated. Two papers comprise various parts of this study. Part I details the ozone model performance and the methodology that was used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…CMAQ was also used to investigate aerosol formation and transport in the Pacific Northwest during July 1-16, 19961-16, (O'Neill et al 2006. The mean fractional bias and error of PM 2.5 mass were within 30% and 50%, respectively, and those of PM 2.5 species concentrations were within the acceptable bound (Boylan et al 2006). Further, effects of spatial variability on CMAQ evaluation found that the uncertainties due to the different spatial scales between the point-observations and volume-averaged simulated concentrations did not significantly affect model errors .…”
mentioning
confidence: 72%
“…CMAQ was also used to investigate aerosol formation and transport in the Pacific Northwest during July 1-16, 19961-16, (O'Neill et al 2006. The mean fractional bias and error of PM 2.5 mass were within 30% and 50%, respectively, and those of PM 2.5 species concentrations were within the acceptable bound (Boylan et al 2006). Further, effects of spatial variability on CMAQ evaluation found that the uncertainties due to the different spatial scales between the point-observations and volume-averaged simulated concentrations did not significantly affect model errors .…”
mentioning
confidence: 72%
“…Historical (24). Detailed information on the modeling system and performance can be found elsewhere (20).…”
Section: Methodsmentioning
confidence: 99%
“…PM also contributes to impaired atmospheric visibility by scattering and absorbing light (Boylan et al, 2006), issues which are discussed in other article.…”
Section: Air Pollutantsmentioning
confidence: 99%